Strategi pendidik yang efektif dan efisien untuk meningkatkan motivasi belajar siswa - Kadrina, Lilatul (Maliki Interdisciplinary Journal, 2025)
Learning motivation is a crucial factor in achieving students' learning outcomes. Therefore, this study will focus on identifying the factors that most influence students' learning motivation and strategies to improve it effectively. Students' learning motivation is influenced by factors within the individual themselves, such as interests, life goals, emotional conditions, and external factors including aspects such as learning methods, school environment, and family support. This means that the optimal role of teachers and parents is very supportive in improving students' learning motivation. Innovation in both project-based learning and the use of digital technology can significantly increase students' learning motivation. The results of the study show that a combination of interesting learning approaches, giving awards, and collaboration between teachers and parents can strengthen students' learning motivation, which in turn can improve their academic achievement. These findings provide an important contribution to the development of more effective learning strategies that are in accordance with the needs of students in the digital era.